Flow and Meaningfulness as Mechanisms of Change in Self-Concept and Well-Being Following a Songwriting Intervention for People in the Early Phase of Neurorehabilitation - Baker, Felicity Anne; Rickard, Nikki; Tamplin, Jeanette; Roddy, Chantal (Frontiers in Human Neuroscience, 2015)
Anecdotal evidence suggests that songwriting assists people with spinal cord injury (SCI) or acquired brain injury (ABI) to explore threats to self-concept, yet studies that explore the mechanisms of change have not been reported. In a pilot study we explored the correlations between changes in self-concept and wellbeing, with mechanisms of flow and meaningfulness of songwriting. Five people with ABI (all male) and 5 SCI (4 males, 1 female) (mean age 38.90 years, SD=13.21), with an average 3 months post injury, participated in a 12-session songwriting program that targeted examination of self-concept. Measures of self-concept, depression, anxiety, emotion regulation, affect, satisfaction with life, and flourishing were collected pre, mid, and post-intervention, and compared with repeated measures of flow and meaningfulness of songwriting. Medium effects were found for changes in self-concept (d = 0.557) and depression (d = 0.682) and approached a medium effect for negative affect (d = 0.491). Improvements in self-concept over time were associated with decreases in depression (rp=-.874, n=9, p<.01), anxiety (rp=-.866, n=9, p<.01) and negative affect (rp=-.694, n=10, p<.05), and an increase in flourishing (rp=+.866, n=9, p<.01) and positive affect (rp=+.731, n=10, p<.05). Strong experiences of flow were not positively correlated with positive changes to self-concept and wellbeing, whereas deriving high levels of meaning were associated with increased negative affect (rp=+.68 p<.05), increased anxiety (rp=+.74, p<0.05) and reduced emotional suppression (rp=-.58, p<.05). These findings show that the targeted songwriting intervention appears to be positively associated with enhanced wellbeing outcomes. However, the findings also suggest that people who find the songwriting process has strong meaning for them might be more likely to start accepting their emotions and as a result experience an increase in anxiety and depression.